Examining factors influencing Muslim young generations decision to choose Islamic banking products - Zabidi, Ahmad (2018)
This study investigates the relationship of Demographic factors, Religion factors, Awareness & knowledge of Islamic bank (IB) products factors and bank reputations factors to young Muslim generation decision to choose Islamic bank products. Demographic defined as the age and gender of the individual. Religion defined as the intrinsic religious orientation more on spirituality of an individual. Awareness and knowledge is viewed as consciousness, recognition or familiarity about Islamic bank products. Bank reputations defined as the general opinion or judgement of the public about a bank. Young generation (youth) defined by the age is those persons between 15 to 24 years old. A research framework model and hypothesis concerning the relationships among the variables - Religion factor, Awareness and Knowledge about IB Products, Bank Reputations and Young generations’ decision to choose IB Products were posited and tested. Data was collected using hand delivery questionnaire survey approach involving three hundred seventy two (372) respondents both male and female of UiTM Puncak Alam Campus undergraduate students. Factor analysis, Pearson correlation, multiple regression methods of data analysis were utilized for hypothesis testing. The results of the correlation revealed that Religion Factor, Awareness and Knowledge about IB Products and Bank Reputations are positively associated with the young Muslim generation decision to choose IB Products. The outcome of this study provides vital information on the influence of the Religion Factor, Awareness and Knowledge about IB Products and Bank Reputations on young Muslim generation decision to choose IB Products. The managerial implication of this study is for the Islamic banking industry to focus on those factors that would have influence to customer decision or specifically the young Muslim generation customer.